2010
DOI: 10.1109/tpwrs.2009.2033931
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Firm Wind Connection to Security Constrained Transmission Networks

Abstract: Abstract-Prudent use of existing transmission capacity could be achieved by an optimal allocation of wind capacity to distinct transmission nodes. The statistical interdependency of geographically separate wind sites and the partially-dispatchable nature of wind power require a collective analysis of all potential wind farms over an extended time-frame in any optimized transmission planning study. The methodology presented in this paper separates this large optimization problem into smaller subtasks, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 25 publications
1
65
0
2
Order By: Relevance
“…As shown in Figure 2, at the high-voltage transmission network (HV-TN), firm [11] and non-firm [12] wind energy penetration can be maximized. It was mentioned in [13] that unit commitment issues and the stability of voltage at a HV-TN have high effects on wind energy losses.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, at the high-voltage transmission network (HV-TN), firm [11] and non-firm [12] wind energy penetration can be maximized. It was mentioned in [13] that unit commitment issues and the stability of voltage at a HV-TN have high effects on wind energy losses.…”
Section: Figurementioning
confidence: 99%
“…It was mentioned in [13] that unit commitment issues and the stability of voltage at a HV-TN have high effects on wind energy losses. Based on [11][12][13], other important factors which influence wind energy losses in a HV-TN were studied in [14]. It was shown that the reverse active power flow from a downstream medium-voltage active distribution network (MV-ADN) could be rejected at the HV-TN level.…”
Section: Figurementioning
confidence: 99%
“…Allocation of optimal wind capacity in power systems with an indication of unit commitment has been addressed in several works using both linear and non-linear OPF [10]- [13]. The authors of [10] propose a method that sequentially increases the wind energy penetration target while updating the unit commitment and wind capacity allocation pattern formulated as a linear problem.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…This network is based on the topology of a subset of the Irish transmission system originally introduced in [10]. The line parameters were altered to represent the 110 kV transmission system.…”
Section: A Test Systemmentioning
confidence: 99%